2020
DOI: 10.1371/journal.pone.0242383
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of mouse IRG1 suggests that cis-aconitate decarboxylase has an open and closed conformation

Abstract: Itaconate, produced as an offshoot of the TCA cycle, is a multifunctional immunometabolite possessing antibacterial, antiviral, immune regulation, and tumor progression activities. The production of itaconate in biological systems is catalyzed by cis-aconitate decarboxylase (CAD, also known as immune responsive gene 1 (IRG1) in mammals). In this study, we solved the structure of IRG1 from Mus musculus (mouse IRG1). Structural comparison analysis revealed that IRG1 can exist in either an open or closed conforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The sulfur atom of Met154 is located at 4.1 Å distance from the Phe381 ring centre (dashed yellow line) at an angle of 68° to the plane of the aromatic ring. The Ile154 residue of the aligned mACOD1 structure of Chun et al 9 (PDB ID code 7BR9) is shown in purple. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The sulfur atom of Met154 is located at 4.1 Å distance from the Phe381 ring centre (dashed yellow line) at an angle of 68° to the plane of the aromatic ring. The Ile154 residue of the aligned mACOD1 structure of Chun et al 9 (PDB ID code 7BR9) is shown in purple. …”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of ACOD1 catalysis includes an opening of the active site by tilting the smaller domain relative to the larger domain (Fig. 1 ) 8 , 9 . The side chains of residues 152 and 154 are located at the interface of the smaller and larger domain, and residue 154 also lines a hydrophobic pocket in the active centre.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations